2020
DOI: 10.3855/jidc.11955
|View full text |Cite
|
Sign up to set email alerts
|

The survival rate of tuberculosis patients in HIV-treated cohort of 2008-2018 in Almaty, Kazakhstan

Abstract: Introduction: HIV/TB comorbidity is responsible for 1.6 million deaths worldwide. HIV/TB control and patients’ survival are still among priorities of the national HIV and TB programs. We aimed to evaluate the HIV/TB survival in connection with TB treatment outcomes and factors influencing life duration of the cohort 2008-2018 in Almaty, Kazakhstan. Methodology: This retrospective cohort study extracted data for all HIV and pulmonary TB adults coinfected during 2008-2018 in Almaty from national registries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
2
6
2
Order By: Relevance
“…CD4 counts were an important risk factor associated with mortality in co-infected patients. Low CD4 counts at the time of detection of TB is known to be associated with poor survival [20]. Indeed, as with our data, many studies have reported higher mortality in co-infected patients with CD4 counts of <200 cells/mm 3 [26,27].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…CD4 counts were an important risk factor associated with mortality in co-infected patients. Low CD4 counts at the time of detection of TB is known to be associated with poor survival [20]. Indeed, as with our data, many studies have reported higher mortality in co-infected patients with CD4 counts of <200 cells/mm 3 [26,27].…”
Section: Discussionsupporting
confidence: 87%
“…As seen in our data, the overall mortality during the course of treatment was 18%; this was higher than the pooled proportion (10.9%) found in the meta-analysis of outcomes of HIV-TB infection [18,19]. Other studies, however, have reported a higher mortality in HIV-TB patients particularly in the initial months after diagnosis of TB [12,20]. Huddart and colleagues [18] have also reported that mortality in the sub-group of HIV-TB co-infected individuals was higher than TB patients; however, there are few reports of mortality from India.…”
Section: Discussioncontrasting
confidence: 56%
“…Over half of the TB/HIV patients from eastern Europe had died during follow-up in our study. This is exceeding the mortality documented in the previous studies reporting long-term follow-up among TB/HIV co-infected patients, where the highest rates described were 5-year mortality at 44% in Kazakhstan and 12-year mortality at 44% in Brazil [4,6]. Other studies from Latin America found five-year all-cause mortality rates in TB/HIV patients between 10 and 14% and a study from China reported a nearly 35% mortality 5 years after completion of TB treatment [3,5,23].…”
Section: Discussionmentioning
confidence: 71%
“…However, data on TB recurrence and long-term mortality among TB/HIV patients in endemic areas is scarce. Studies from Latin America, Central Asia and China found 5-year all-cause mortality rates in TB/HIV patients between 10 and 44% [3][4][5][6]. However, to the best of our knowledge, no study has assessed causes of deaths and/or whether they were TB-related.…”
Section: Introductionmentioning
confidence: 97%
“…It can be modeled using the Cox proportional hazard regression method. Cox regression is one of the popular methods in survival analysis [3].…”
Section: Introductionmentioning
confidence: 99%